The Use of English Punctuation in Improving Students’ Writing Skills at The Sixth Semester of Letters of UMI Makassar - Sunardi Hasyim; Burhanuddin Burhanuddin; Sumarni Hafid (Tamaddun Life, 2017)
The research entitled The use of English Punctuation in improving Students writing skills at the sixth semester of Faculty of Letters of UMI Makassar. This study aims to describe student`s error of using punctuation in English text. The study is conducted to students at the semester six of English Department. The researcher analyzed the error in the use of punctuation itself, because good punctuation is essential in clear and effective writing especially in academic writing. It was correlated to Jeremy’s theory (2004,p.49) stated that using punctuation correctly is one of the important skill in writing.. There are two problems of this study; how the students’ errors of using punctuation in English text are and what cause of error in using punctuation. The researcher used qualitative method in this study. Punctuation marks that are presented in this research are comma, full stop, hyphen, apostrophe, question mark, quotation mark, and exclamation mark. As a result, the researcher found that comma is most common error made by the English Department student during the sixth semester. In the data analysis, the writer described that the sixth Semester Students’ of the English Department have low achievement in using English Punctuation. The low achievement they have is primarily caused by their errors that are still made by students’ in using English Punctuation, they are also influenced by the following factors : 1. The students’ basic knowledge in using English punctuation is not sufficient, 2. The interest of the students’ in learning and doing the exercises of the use of English punctuation is low, and 3. The English punctuation is very complex and difficult to the students’.